2021
DOI: 10.3390/children8070536
|View full text |Cite
|
Sign up to set email alerts
|

Association between Overweight and Diet Diversity Score: A Cross-Sectional Study Conducted among Tunisian Children

Abstract: Aim: This study explored the association between the diet diversity score (DDS) and overweight among Tunisian children. Methods: A representative sample of children living in Greater Tunis was selected based on a two-stage clustered sampling design. A total of 1200 children (3–9 years) were recruited. Dietary assessment was realized using a 24 h dietary recall. Anthropometric measurements were realized, and overweight was defined according to the World Health Organization standards. Logistic regression was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Children’s dietary intake was assessed face-to-face with mothers or caretakers for children during home visits using 24-h dietary recall and the diet history for the month preceding the survey [ 13 ]. Trained dieticians recorded data on the types of all foods and drinks consumed by children.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children’s dietary intake was assessed face-to-face with mothers or caretakers for children during home visits using 24-h dietary recall and the diet history for the month preceding the survey [ 13 ]. Trained dieticians recorded data on the types of all foods and drinks consumed by children.…”
Section: Methodsmentioning
confidence: 99%
“…Data on the level of education and occupation of children’s mother and the head of household were collected by questionnaire. The economic level of the household was assessed using an asset-based proxy and classified as low, medium or high according to tertiles of this index [ 13 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Children dietary intake was assessed face-to-face with mothers or caretakers for children during home visits using 24-hours recall and the diet history for the month preceding the survey [13].…”
Section: Dietary Intake Assessmentmentioning
confidence: 99%
“…Data on level of education and occupation of children's mother and the head of household were collected by questionnaire. The economic level of the household was assessed using an asset based proxy and classified as low, medium or high according to tertiles of this index [13,20].…”
Section: Socioeconomic and Demographic Characteristicsmentioning
confidence: 99%
“…Several scientific works confirmed that the Mediterranean diet, formerly adopted in the Mediterranean countries, is considered as a nutritional and healthy food model with important benefits for the population (Ridolfi et al, 2020;Dogui et al, 2021;Med diet project, 2017). Declared an "intangible heritage of humanity" in 2010, the Mediterranean model is not a homogeneous model in the Mediterranean area due to regional social, cultural and economic variations (UNESCO, 2010; Khaldi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%